CN1069247C - Amalgamation for prodn. of zinc amalgam powder - Google Patents
Amalgamation for prodn. of zinc amalgam powder Download PDFInfo
- Publication number
- CN1069247C CN1069247C CN92103622A CN92103622A CN1069247C CN 1069247 C CN1069247 C CN 1069247C CN 92103622 A CN92103622 A CN 92103622A CN 92103622 A CN92103622 A CN 92103622A CN 1069247 C CN1069247 C CN 1069247C
- Authority
- CN
- China
- Prior art keywords
- zinc
- amalgamation
- zinc powder
- mercury
- powder
- Prior art date
- Legal status (The legal status is an assumption and is not a legal conclusion. Google has not performed a legal analysis and makes no representation as to the accuracy of the status listed.)
- Expired - Fee Related
Links
- HCHKCACWOHOZIP-UHFFFAOYSA-N Zinc Chemical compound [Zn] HCHKCACWOHOZIP-UHFFFAOYSA-N 0.000 title claims abstract description 109
- 238000005267 amalgamation Methods 0.000 title claims abstract description 50
- 229910000497 Amalgam Inorganic materials 0.000 title claims abstract description 36
- 239000000843 powder Substances 0.000 title claims description 17
- 229910052725 zinc Inorganic materials 0.000 title description 38
- 239000011701 zinc Substances 0.000 title description 38
- QSHDDOUJBYECFT-UHFFFAOYSA-N mercury Chemical compound [Hg] QSHDDOUJBYECFT-UHFFFAOYSA-N 0.000 claims abstract description 39
- 229910052753 mercury Inorganic materials 0.000 claims abstract description 39
- XLYOFNOQVPJJNP-UHFFFAOYSA-N water Substances O XLYOFNOQVPJJNP-UHFFFAOYSA-N 0.000 claims abstract description 25
- 238000000034 method Methods 0.000 claims abstract description 24
- 238000010791 quenching Methods 0.000 claims abstract description 10
- 230000000171 quenching effect Effects 0.000 claims abstract description 10
- 238000000889 atomisation Methods 0.000 claims abstract description 4
- KWYUFKZDYYNOTN-UHFFFAOYSA-M Potassium hydroxide Chemical compound [OH-].[K+] KWYUFKZDYYNOTN-UHFFFAOYSA-M 0.000 claims description 27
- 238000003756 stirring Methods 0.000 claims description 26
- 238000006243 chemical reaction Methods 0.000 claims description 16
- 229910001297 Zn alloy Inorganic materials 0.000 claims description 10
- 239000007864 aqueous solution Substances 0.000 claims description 9
- 238000004519 manufacturing process Methods 0.000 claims description 6
- 238000002156 mixing Methods 0.000 claims description 6
- 239000007788 liquid Substances 0.000 claims description 5
- 239000000203 mixture Substances 0.000 claims description 3
- 238000001035 drying Methods 0.000 abstract description 7
- 238000012545 processing Methods 0.000 abstract description 6
- 238000005406 washing Methods 0.000 abstract description 5
- 230000000694 effects Effects 0.000 abstract description 3
- 230000005611 electricity Effects 0.000 abstract description 2
- 238000007599 discharging Methods 0.000 abstract 1
- 239000003595 mist Substances 0.000 abstract 1
- LUMVCLJFHCTMCV-UHFFFAOYSA-M potassium;hydroxide;hydrate Chemical compound O.[OH-].[K+] LUMVCLJFHCTMCV-UHFFFAOYSA-M 0.000 abstract 1
- XLOMVQKBTHCTTD-UHFFFAOYSA-N Zinc monoxide Chemical compound [Zn]=O XLOMVQKBTHCTTD-UHFFFAOYSA-N 0.000 description 8
- 239000003513 alkali Substances 0.000 description 7
- 230000015572 biosynthetic process Effects 0.000 description 7
- 239000011265 semifinished product Substances 0.000 description 7
- 239000002245 particle Substances 0.000 description 5
- UFHFLCQGNIYNRP-UHFFFAOYSA-N Hydrogen Chemical compound [H][H] UFHFLCQGNIYNRP-UHFFFAOYSA-N 0.000 description 4
- 229910045601 alloy Inorganic materials 0.000 description 4
- 239000000956 alloy Substances 0.000 description 4
- 239000002585 base Substances 0.000 description 4
- 230000018044 dehydration Effects 0.000 description 4
- 238000006297 dehydration reaction Methods 0.000 description 4
- 229910052739 hydrogen Inorganic materials 0.000 description 4
- 239000001257 hydrogen Substances 0.000 description 4
- 239000012535 impurity Substances 0.000 description 4
- 235000012054 meals Nutrition 0.000 description 4
- 239000002244 precipitate Substances 0.000 description 4
- 239000000047 product Substances 0.000 description 4
- 238000012216 screening Methods 0.000 description 4
- 239000007921 spray Substances 0.000 description 4
- 239000011787 zinc oxide Substances 0.000 description 4
- PTFCDOFLOPIGGS-UHFFFAOYSA-N Zinc dication Chemical compound [Zn+2] PTFCDOFLOPIGGS-UHFFFAOYSA-N 0.000 description 3
- 230000009286 beneficial effect Effects 0.000 description 3
- 238000002474 experimental method Methods 0.000 description 3
- 238000005246 galvanizing Methods 0.000 description 3
- 229910052738 indium Inorganic materials 0.000 description 3
- APFVFJFRJDLVQX-UHFFFAOYSA-N indium atom Chemical compound [In] APFVFJFRJDLVQX-UHFFFAOYSA-N 0.000 description 3
- 230000001590 oxidative effect Effects 0.000 description 3
- 229920006395 saturated elastomer Polymers 0.000 description 3
- 239000002893 slag Substances 0.000 description 3
- 239000000126 substance Substances 0.000 description 3
- 229960001296 zinc oxide Drugs 0.000 description 3
- 241000196324 Embryophyta Species 0.000 description 2
- 229910000645 Hg alloy Inorganic materials 0.000 description 2
- VEXZGXHMUGYJMC-UHFFFAOYSA-N Hydrochloric acid Chemical compound Cl VEXZGXHMUGYJMC-UHFFFAOYSA-N 0.000 description 2
- 240000005373 Panax quinquefolius Species 0.000 description 2
- 235000003140 Panax quinquefolius Nutrition 0.000 description 2
- VYPSYNLAJGMNEJ-UHFFFAOYSA-N Silicium dioxide Chemical compound O=[Si]=O VYPSYNLAJGMNEJ-UHFFFAOYSA-N 0.000 description 2
- 238000004090 dissolution Methods 0.000 description 2
- 229910052751 metal Inorganic materials 0.000 description 2
- 230000007935 neutral effect Effects 0.000 description 2
- 230000003647 oxidation Effects 0.000 description 2
- 238000007254 oxidation reaction Methods 0.000 description 2
- 238000000053 physical method Methods 0.000 description 2
- 238000010301 surface-oxidation reaction Methods 0.000 description 2
- 229910052716 thallium Inorganic materials 0.000 description 2
- BKVIYDNLLOSFOA-UHFFFAOYSA-N thallium Chemical compound [Tl] BKVIYDNLLOSFOA-UHFFFAOYSA-N 0.000 description 2
- -1 this Chemical compound 0.000 description 2
- QGZKDVFQNNGYKY-UHFFFAOYSA-O Ammonium Chemical compound [NH4+] QGZKDVFQNNGYKY-UHFFFAOYSA-O 0.000 description 1
- GYHNNYVSQQEPJS-UHFFFAOYSA-N Gallium Chemical compound [Ga] GYHNNYVSQQEPJS-UHFFFAOYSA-N 0.000 description 1
- 235000005035 Panax pseudoginseng ssp. pseudoginseng Nutrition 0.000 description 1
- 150000008044 alkali metal hydroxides Chemical class 0.000 description 1
- 238000004458 analytical method Methods 0.000 description 1
- 229910052793 cadmium Inorganic materials 0.000 description 1
- BDOSMKKIYDKNTQ-UHFFFAOYSA-N cadmium atom Chemical compound [Cd] BDOSMKKIYDKNTQ-UHFFFAOYSA-N 0.000 description 1
- 238000001311 chemical methods and process Methods 0.000 description 1
- 230000000052 comparative effect Effects 0.000 description 1
- 230000007812 deficiency Effects 0.000 description 1
- 230000008021 deposition Effects 0.000 description 1
- 238000007598 dipping method Methods 0.000 description 1
- 239000003792 electrolyte Substances 0.000 description 1
- 230000002708 enhancing effect Effects 0.000 description 1
- 230000007613 environmental effect Effects 0.000 description 1
- 230000002349 favourable effect Effects 0.000 description 1
- 229910052733 gallium Inorganic materials 0.000 description 1
- 238000009689 gas atomisation Methods 0.000 description 1
- 235000008434 ginseng Nutrition 0.000 description 1
- 230000005484 gravity Effects 0.000 description 1
- 238000010438 heat treatment Methods 0.000 description 1
- 230000036571 hydration Effects 0.000 description 1
- 238000006703 hydration reaction Methods 0.000 description 1
- 238000004900 laundering Methods 0.000 description 1
- WABPQHHGFIMREM-UHFFFAOYSA-N lead(0) Chemical compound [Pb] WABPQHHGFIMREM-UHFFFAOYSA-N 0.000 description 1
- 239000002184 metal Substances 0.000 description 1
- 230000000704 physical effect Effects 0.000 description 1
- 238000011160 research Methods 0.000 description 1
- 239000000779 smoke Substances 0.000 description 1
- 239000000243 solution Substances 0.000 description 1
- 238000012360 testing method Methods 0.000 description 1
- 238000004065 wastewater treatment Methods 0.000 description 1
Classifications
-
- H—ELECTRICITY
- H01—ELECTRIC ELEMENTS
- H01M—PROCESSES OR MEANS, e.g. BATTERIES, FOR THE DIRECT CONVERSION OF CHEMICAL ENERGY INTO ELECTRICAL ENERGY
- H01M4/00—Electrodes
- H01M4/02—Electrodes composed of, or comprising, active material
- H01M4/36—Selection of substances as active materials, active masses, active liquids
- H01M4/38—Selection of substances as active materials, active masses, active liquids of elements or alloys
- H01M4/42—Alloys based on zinc
-
- Y—GENERAL TAGGING OF NEW TECHNOLOGICAL DEVELOPMENTS; GENERAL TAGGING OF CROSS-SECTIONAL TECHNOLOGIES SPANNING OVER SEVERAL SECTIONS OF THE IPC; TECHNICAL SUBJECTS COVERED BY FORMER USPC CROSS-REFERENCE ART COLLECTIONS [XRACs] AND DIGESTS
- Y02—TECHNOLOGIES OR APPLICATIONS FOR MITIGATION OR ADAPTATION AGAINST CLIMATE CHANGE
- Y02E—REDUCTION OF GREENHOUSE GAS [GHG] EMISSIONS, RELATED TO ENERGY GENERATION, TRANSMISSION OR DISTRIBUTION
- Y02E60/00—Enabling technologies; Technologies with a potential or indirect contribution to GHG emissions mitigation
- Y02E60/10—Energy storage using batteries
Landscapes
- Chemical & Material Sciences (AREA)
- Chemical Kinetics & Catalysis (AREA)
- Electrochemistry (AREA)
- General Chemical & Material Sciences (AREA)
- Battery Electrode And Active Subsutance (AREA)
Abstract
The present invention provides a wet-type amalgamation method for preparing amalgam zinc powder used for alkaline cells, which has the advantage of saving time, electricity and water. In the method, zinc powder and mercury are immersed in potassium hydroxide water solutions of which the concentration is from 15 to 50% (weight) or pure water and are rapidly thoroughly stirred in a short time. Wet-type amalgamation treatment carried out for the zinc powder prepared in an air atomization method of using water mist or water as quenching media according to the method of the present invention can achieve the following effects: (1) the time of amalgamation can be shortened to about 5 minutes from original more than 1 hour; (2) a large quantity of water is not needed for washing after amalgamation by using the pure water as amalgamation media; (3) the gassing quantity of the amalgam zinc powder containing 0.5 to 3% (weight) of mercury is from 0.01 to 0.03 ml/5g. 3d through the treatment of the processing steps of washing (to neutrality), dewatering, drying, etc. An LR20 battery (home-made) made from partial amalgam zinc powder is continuously discharged by a 3.9 ohms of resistor to 1.0V in discharging time from 22 to 24 hours.
Description
The present invention relates to a kind of wet type amalgamation method of making the amalgam zinc powder, it is specially adapted to make the used amalgam zinc powder of Zinc-alkaline battery.
For control Zinc-alkaline battery existing the dissolving and the separating out of hydrogen certainly of zinc, and taked the anticathode zinc powder to carry out the measure of amalgamation processing.But along with the continuous enhancing of people to environmental consciousness, for reducing the caused public hazards of pollution of mercury, an urgent demand reduces the mercury content of negative pole zinc (amalgam zinc powder) in the Zinc-alkaline battery.
The production method of amalgam zinc powder is a lot, at present following two class methods of industrial common use:
1, liquation amalgamation
In galvanizing zinc, add a certain amount of mercury, also can add several beneficial elements, compressed gas atomization forms the amalgam zinc powder.
2, powder amalgamation
Mercury less zinc powder or its alloy mix with mercury or mercury alloy in certain medium (or vacuum) lining (or state), and by stirring, reaction forms the amalgam zinc powder.This method is divided into dry type and wet type amalgamation again.
Relatively, though liquation amalgamation and dry type amalgamation can reach the purpose (the mercurous 1-3% of dropping to of zinc powder) of expection precipitate, but problem is all can produce a large amount of mercury vapour in the amalgamation course of reaction, must have specific device to reclaim remaining gaseous mercury like this, otherwise the public hazards that pollution caused of mercury are inevitable.So, adopt wet type amalgamation method relatively still favourable, operator's the sense of security also can strengthen in the production process like this.
The Japan Patent spy opens clear 63-86806 communique and the 60-146456 communique has all been introduced wet type amalgamation method, all be to adopt the KOH aqueous solution to make the amalgamation medium, the former concentration of lye is 3%, latter's concentration of lye is 30%, all be after putting into zinc powder or Zinc alloy powder in the alkali lye, splash into mercury while stirring and react and form the amalgam zinc powder.By add a certain amount of beneficial element in the zinc-base body, the both can reach the purpose of expection precipitate.But problem is: (one) can not stir at short notice, react and form the amalgam zinc powder, is generally 60-180 minute such as the former; (2) latter is the purpose that reaches the expection precipitate, need add valuable gallium (Ga) and thallium (Tl) in the zinc-base body, and still extremely harmful to the health of human body element of thallium.
Open the introduction of clear 55-128553 communique according to another the spy, for fear of because of using the aqueous solution such as alkali metal hydroxide, hydrochloric acid, ammonium to make after the loss of amalgamation zinc that medium brings and the amalgamation the high problem of expense in the wastewater treatment process, and adopt pure water to carry out the amalgamation processing as medium.The method is that zinc powder is put in the reaction pot, stir energetically for a long time after the adding, physical actions such as reaction pot and zinc powder, agitator arm and zinc powder, zinc powder and zinc powder clash into each other, friction, vibration, make destroyed the removing of zinc particle surface oxidation zinc film, slowly add mercury at last and carry out the amalgamation processing.But problem is: removing zinc powder surface oxidation zinc film need finish with mechanical means, has so both expended electric power, uses a large amount of high-quality water again, and the time that amalgamation is stirred, reaction forms the amalgam zinc powder is still grown (35-50 minute).
The present invention is in order to solve the deficiency of above-mentioned existence, wet type amalgamation method is improved, a purpose is to stir, react formation amalgam zinc powder in the short time, and another purpose is to wash without massive laundering before and after the amalgamation, and still can reach the purpose of expection precipitate.
The present invention is achieved in that
The inventor thinks through a large amount of experiments, research, zinc directly contacts generation zinc amalgam alloy with mercury and is not difficult, when but zinc powder mixes with mercury, if the zinc particle surface forms zinc-oxide film (hereinafter to be referred as " film "), will hinder zinc to contact with the direct of mercury, zinc powder and mercury are difficult to form alloy so, unless " film " is removed.So, want to make zinc powder and mercury to form alloy, the one, must remove " film ", the 2nd, do not form " film ".Just be based on this 2 considerations, producing following scheme.
At first, in order to remove " film ", the inventor has carried out repeatedly experimental studies have found that the employing concentration range is that the potassium hydroxide aqueous solution of 15-50% is made the amalgamation medium, zinc powder is mixed with mercury and abundant the stirring 0.5-5 minute by proportioning, can react formation amalgam zinc powder.Adopt this scheme to carry out amalgamation and handle, solid-to-liquid ratio is controlled at 1: 2~2: 1 (weight ratio), and reaction temperature is controlled at 20-120 ℃, and stirring frequency is controlled at 200~300 times/minute.During alkali lye submergence zinc powder, because of " film " is removed, mercury directly contacts with zinc, has quickened the amalgamation reaction, can be at a few minutes or internal reaction formation in tens seconds amalgam zinc powder, even also can finish the amalgamation reaction at a lower temperature by abundant stirring.Found through experiments, before amalgamate, zinc powder immerse in the alkali lye time length be disadvantageous, preferably zinc powder and mercury add fully stirring in the alkali lye simultaneously, can improve the concentration of zinc powder surface mercury like this, thus the release of hydrogen can control battery effectively and form the time.
Secondly, in order not form " film ", the inventor has carried out after the repeatedly experiment a surprising discovery being arranged, adopt compressed air atomizing zinc method, the zinc drop that will atomize directly sprays into quenching in the water, and the wet zinc powder that is obtained is earlier without drying process, directly in pure water, mix and abundant the stirring 1~15 minute, can react formation amalgam zinc powder with mercury.Adopt this scheme to carry out amalgamation and handle, solid-to-liquid ratio is controlled at 1: 2~1: 1 (weight ratio), and reaction temperature is controlled at 35~65 ℃, and stirring frequency is controlled at 1000~2000 rev/mins.The zinc drop that will atomize directly sprays into quenching in the water, earlier without drying process, its particle surface of wet zinc powder that is obtained can not cover by complete oxidized zinc, thus zinc can directly contact with mercury, thereby also can by stir in the short time, reaction forms the amalgam zinc powder.In order to reduce oxidation, wet zinc powder is not long standing time, and preferably the wet zinc powder of newborn output directly carries out mercuration and handles after meal and fine powder are removed in screening.According to above-mentioned two schemes, by adding beneficial elements such as lead, indium in the zinc-base body, the amalgam zinc powder of the low mercury content that is obtained still keeps the feature of the amalgam zinc powder of original high mercury content.
One of main feature of the present invention is to stir, react formation amalgam zinc powder in the short time at a lower temperature, and minimum humidity can drop to below 30 ℃, and the shortest mixing time can drop to below 1 minute.Relatively both electric energy can be saved, work efficiency can be improved again.In addition, handle, directly drop into battery production usefulness after the amalgamation if carry out amalgamation in battery producer, both high-quality water washings in a large number, also without drying and dehydrating, cost can reduce greatly like this.Another outstanding advantage of the present invention is to make the amalgamation medium with pure water, and because of not needing to remove " film " with chemistry or physical method, so cost also can reduce greatly, and because of not using alkali in the production process, operator's the sense of security strengthens naturally.
Be easy to though remove " film " with chemical method, a process also will be arranged, removing " film " when beginning, when middle and when end, adding mercury respectively and carry out amalgamation and handle, the effect that is produced is different.Zinc is the higher metal of electron affinity, directly contacts with mercury and is easy to reaction formation amalgam.When so zinc powder mixes with mercury, do not removing " film " preceding or when beginning, zinc particle just should fully contact by certain proportioning with its surperficial mercury, in case " film " is dissolved, zinc and mercury is haptoreaction immediately, the amalgamation zinc powder of Xing Chenging is the most uniform like this, and the amalgamation effect is best.So, to stir by removing with chemical method in " film " short time, it is fully passable that reaction forms the amalgam zinc powder.
Zinc is in water, the zinc ion of hydrone that polarity is big and formation lattice is attracted each other and hydration is taken place, part forms the aquation zinc ion and dissolves, and is subjected to the attraction of the superfluous negative electrical charge of zinc surface, and the aquation zinc ion also will deposit to zinc surface, finally reach the dynamic equilibrium of dissolving and deposition, if other impurity is arranged in the zinc-base body, hydrogen ultra-voltage on impurity is less, and then dissolution velocity can sharply increase, otherwise the ultra-voltage of hydrogen on impurity is higher, and dissolution velocity will reduce greatly.So by the kind and the content of control impurity, improveing the oxidation that atomization process prevents zinc powder simultaneously is effectively, does not need fully before the amalgamation to consider to remove " film " with chemical method and physical method.From example, be specifically described below.
Example 1-example 5:
At first, the compressed air atomizing zinc legal system that adopts water smoke to make quenching media is got Zinc alloy powder.
(1) No. 0 smart zinc is melted to about 500 ℃, removes oxidizing slag, add lead, indium and cadmium element.
(2) galvanizing zinc is that Mannesmann's type nozzle of 2.8 millimeters atomizes by leaking the eye diameter, and the quenching media temperature is about 40 ℃.
(3) wet zinc powder is by centrifuge dewatering, and after the dehydration of rotary kiln heat drying, meal and fine powder are removed in screening, is left to be semi-finished product.
Secondly, semi-finished product are that 40% potassium hydroxide aqueous solution carries out the amalgamation processing with the saturated concentration of zinc oxide.
(4) semi-finished product fully stir stirring frequency 200-300 time/minute with mercury simultaneously according to beaker (capacity the is 400ml) lining that proportioning adds Sheng 100ml alkali lye with quartz glass bar.
At last, obtain finished product amalgam zinc powder after washing (to neutral), dehydration, the dried.The amalgam zinc powder gassing rate performance of the mercurous 1-2% of gained reaches following index (seeing Table 1).Example 6-example 8:
At first, adopt compressed air atomizing zinc method, atomizing zinc drop sprays in the water quenching and produces Zinc alloy powder
(1) No. 0 smart zinc is melted to about 600 ℃, removes oxidizing slag, add the metallic lead element.
(2) galvanizing zinc is that Mannesmann's type nozzle of 2.8 millimeters atomizes about 65 ℃ of quenching media temperature by leaking the eye diameter.
(3) after wet zinc powder dewatered by centrifuge dewatering, rotary kiln heat drying, meal and fine powder were removed in screening, and-40-120 order is semi-finished product.
Then, carrying out amalgamation in the 15-50% potassium hydroxide aqueous solution handles.
(4) 100 gram semi-finished product zinc powders add by proportioning in the beaker (capacity is 400ml) of containing 100ml alkali lye with mercury, stir about 1 minute stirring frequency 200-300 time/minute simultaneously with quartz glass bar.
At last, obtain finished product amalgam zinc powder after washing (to neutral), dehydration, the dried.The amalgam zinc powder gassing rate performance of gained mercurous about 1% reaches following index (seeing Table 2).Example 9-example 14
At first adopt compressed air atomizing zinc method, atomizing zinc drop sprays in the water quenching and produces Zinc alloy powder.
(1) No. 0 smart zinc is melted to about 600 ℃, removes oxidizing slag and add metallic element lead, indium.
(2) the zinc fused solution is that 2.0 millimeters Mannesmann's type nozzles atomize by leaking the eye diameter, about 65 ℃ of quenching media temperature.
(3) wet zinc powder is removed meal and fine powder by wet screening, and-40-120 order particle is semi-finished product.
Then, semi-finished product carry out the amalgamation processing in pure water.
(4) will wet zinc powder and mercury or mercury alloy by in the proportioning adding 300ml pure water, the container that is filled with water is the beaker of 1000m, little mixer (vertical) with 40W stirs, solid-to-liquid ratio is 1: 2-1: 1 (weight), water temperature 35-65 ℃, stirring frequency is 1000-2000 rev/min, mixing time 1-15 minute.
At last, obtain finished product amalgam zinc powder through centrifuge dewatering, drying or vacuumize dehydration back.The amalgam zinc powder of the mercurous 0.5-3% of gained, gassing rate and discharge performance reach following index (see Table 3 and table 4).
Table 1
Annotate: A, B carry out the amalgamating situation of dry method for zinc powder not of the same race, and amalgamation is to begin heating under vacuum state, and intensification 0.5-1 hour, constant temperature 2-2.5 hour, container was similar to spheroid, rotary speed 9n/min.
| Sequence number | Batching (g) | The amalgamation condition | Gassing rate (ml/5g.3d) | |||
| Zinc powder | Mercury | Temperature (℃) | Granularity (micron) | Mixing time (branch) | ||
| 1 | 50 | 0.5 | 120 | 88-177 | 1 | 0.03 |
| 2 | 100 | 2 | 120 | 88-177 | 1.5 | 0.02 |
| 3 | 100 | 1.3 | 60 | 125-425 | 5 | 0.02 |
| 4 | 200 | 1.4 | 40 | 125-425 | 0.5 | 0.03 |
| 5 | 100 | 2 | 20 | 125-425 | 3 | 0.03 |
| A | Mercurous 6.5% | Normal temperature-90 ℃ | 125-425 | 180 | 0.03 | |
| B | Mercurous 6.5% | Normal temperature-140 ℃ | 125-425 | 180 | 0.03 | |
Table 2
Annotate: 1, C is the special embodiment that opens clear 63-86806 communique.Gassing rate was measured at 60 ℃ of constant temperature in 30 days.
| Sequence number | Batching (g) | The amalgamation condition | Gassing rate (ml/5g.3d) | |||
| Zinc powder | Mercury | KOH concentration % | Temperature (℃) | Granularity (micron) | ||
| 6 | 100 | 0.8 | 15 | 25 | 25-425 | 0.03 |
| 7 | 100 | 1.1 | 30 | 25 | 125-425 | 0.02 |
| 8 | 100 | 1 | 50 | 25 | 125-425 | 0.025 |
| C | Mercurous 1.21% | 3 | Room temperature | 125-425 | 0.75 | |
| D | Mercurous 1.0% | 30 | Room temperature | 125-425 | 0.017 | |
2, D is the special embodiment A of opening clear 60-146456 communique.Gassing rate is measured: it is in 40% the KOH electrolyte with the saturated concentration of ZnO that the 10g zinc powder is put into 10ml, 45 ℃ of placements 3 months down.
Table 3
Annotate: E is the special embodiment one that opens clear 55-128553 communique.Gassing rate is to be that (temperature is 45 ℃) dipping produced after 3 months in 35% the KOH aqueous solution in concentration.
| Sequence number | Batching (g) | The amalgamation condition | Gassing rate (ml/5g.3d) | Apparent gravity (g/cn 3) | ||
| Zinc powder | Mercury | Reaction temperature (℃) | Mixing time (branch) | |||
| 9 | 850 | 13 | 50-65 | 15 | 0.03 | 3.52 |
| 10 | 850 | 17 | 50-60 | 10 | 0.02 | 3.55 |
| 11 | 850 | 13 | 45-50 | 5 | 0.01 | 3.56 |
| 12 | 500 | 5 | 40-45 | 4 | 0.01 | 3.46 |
| 13 | 500 | 2.5 | 43-45 | 3 | 0.03 | 3.38 |
| 14 | 500 | 10 | 35-36 | 1 | 0.015 | 3.42 |
| E | 25000 | 2000 | 50 | 50 | 1.0-1.3ml | |
Table 4
Annotate: (1) sequence number 1-4 is tested by Guangzhou Battery Factory, and 5-6 converges the test of bright Battery Plant by Shanghai, and 7-8 is tested by Nan Ping, Fujian Battery Plant;
| Sequence number | Kind | Negative pole zinc mercurous (%) | Discharge system | Discharge time (h) |
| 1 | LR20 | 3 | 3.9 Europe CONT EPV=1.0V | 22.6 |
| 2 | LR20 | 2 | The same | 23.6 |
| 3 | LR20 | 1.5 | The same | 22.9 |
| 4 | LR20 | 1 | The same | 23 |
| 5 | LR6 | 1.5 | 10 Europe CONT EPV=0.9V | 16.15 |
| 6 | LR6 | 1.0 | The same | 16.08 |
| 7 | LR6 | 1.0 | 3.9 Europe 30M/DAY EPV=0.9V | 5.4 |
| 8 | LR6 | 1.0 | 75 Europe CONT EPV=0.9V | 136 |
| F | LR20 | / | 3.9 Europe 30M/DAY EPV=0.9V | 21 |
| G | LR6 | / | 10 Europe CONT EPV=0.9V | 13.6-15.8 |
| H | LR6 | / | 75 Europe 240M/DAY EPV=0.9V | 122-136 |
| I | LR6 | / | 3.9 Europe 60M/DAY EPV=0.8V | 4.8-6.0 |
(2) Comparative Example F-I is from battery magazine, and wherein F sees 87 years 2 phases, 22 pages of figure I0-D, and G-I sees 87 years 3 phases 26 page table 4.
Illustrate: (1) sequence number 1-14 (not comprising C, D, E), the gassing rate condition determination is: it was in 40% the potassium hydroxide aqueous solution with the saturated concentration of zinc oxide that 5g amalgam zinc powder is immersed 60ml, 45 ℃ of constant temperature 72 hours.
(2) the described percentage of this specification all is weight percentage.
(3) the described pure water of this specification is meant that electricity consumption ginseng analyses the qualified product that instrument is produced.
(4) the described No. 0 smart zinc of this specification is the GB470-1983 regulation.
Claims (4)
1, a kind of being applicable to made the wet type amalgamation method of Zinc-alkaline battery with the amalgam zinc powder, and it is to make the amalgamation medium with the high concentration potassium hydroxide aqueous solution, and the atomizing Zinc alloy powder is mixed with mercury, and by stirring, reaction forms the amalgam zinc powder, it is characterized in that:
(a) make the amalgamation medium with concentration for the 15-50% potassium hydroxide aqueous solution,
(b) with said amalgamation medium submergence Zinc alloy powder and mercury, begin simultaneously to stir,
(c) mixing time is 0.5-5 minute.
2, according to the described method of claim 1, it is characterized in that:
(d) produce by the compressed air atomization at Zinc alloy powder described in (b);
(e) solid-to-liquid ratio is 1 in (b): 2-2: 1 (weight), temperature are 20-120 ℃;
(f) stirring frequency is 200-300 time/minute in (c).
3, a kind of being applicable to made the wet type amalgamation method of Zinc-alkaline battery with the amalgam zinc powder, and it is to make the amalgamation medium with pure water, and zinc powder is mixed with mercury, and by stirring, reaction forms the amalgam zinc powder, it is characterized in that:
(1) zinc powder is the hygrometric state Zinc alloy powder that new production is come out,
(2) in pure water, mix with mercury with said hygrometric state Zinc alloy powder, begin simultaneously to stir,
(3) mixing time is 1-15 minute.
4, according to the described method of claim 3, it is characterized in that:
(4) be to produce at Zinc alloy powder described in (1) by the compressed air atomization that water is made quenching media
(5) solid-to-liquid ratio is 1 in (2): 2-1: 1 (weight), temperature are 35-65 ℃;
(6) stirring frequency is 1000-2000 rev/min in (3).
Priority Applications (1)
| Application Number | Priority Date | Filing Date | Title |
|---|---|---|---|
| CN92103622A CN1069247C (en) | 1992-05-07 | 1992-05-07 | Amalgamation for prodn. of zinc amalgam powder |
Applications Claiming Priority (1)
| Application Number | Priority Date | Filing Date | Title |
|---|---|---|---|
| CN92103622A CN1069247C (en) | 1992-05-07 | 1992-05-07 | Amalgamation for prodn. of zinc amalgam powder |
Publications (2)
| Publication Number | Publication Date |
|---|---|
| CN1078185A CN1078185A (en) | 1993-11-10 |
| CN1069247C true CN1069247C (en) | 2001-08-08 |
Family
ID=4940327
Family Applications (1)
| Application Number | Title | Priority Date | Filing Date |
|---|---|---|---|
| CN92103622A Expired - Fee Related CN1069247C (en) | 1992-05-07 | 1992-05-07 | Amalgamation for prodn. of zinc amalgam powder |
Country Status (1)
| Country | Link |
|---|---|
| CN (1) | CN1069247C (en) |
Families Citing this family (1)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| CN109888182A (en) * | 2019-01-25 | 2019-06-14 | 天津理工大学 | In-situ protected alkali metal electrode, preparation method and application |
Citations (1)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| JPS55128553A (en) * | 1979-03-28 | 1980-10-04 | Nippon Suigin Yakuhin Kogyo Kk | Manufacture of amalgamated zinc powder |
-
1992
- 1992-05-07 CN CN92103622A patent/CN1069247C/en not_active Expired - Fee Related
Patent Citations (1)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| JPS55128553A (en) * | 1979-03-28 | 1980-10-04 | Nippon Suigin Yakuhin Kogyo Kk | Manufacture of amalgamated zinc powder |
Also Published As
| Publication number | Publication date |
|---|---|
| CN1078185A (en) | 1993-11-10 |
Similar Documents
| Publication | Publication Date | Title |
|---|---|---|
| CN106684351B (en) | A kind of nickel-cobalt-manganese ternary presoma and preparation method thereof | |
| Ma et al. | Recycling lead from spent lead pastes using oxalate and sodium oxalate and preparation of novel lead oxide for lead-acid batteries | |
| CN1117405C (en) | Non-sintered nickel electrode for alkaline storage battery, alkaline storage battery including the same, and method for production of non-sintered nickel electrode for alkalind storage battery | |
| CN101760757B (en) | Method for producing lead by electrolytic alkaline leaching of lead sulfate material | |
| WO2016049994A1 (en) | Lead paste desulfurization method based on grinding mechanism | |
| Ma et al. | Preparation of high-purity lead oxide from spent lead paste by low temperature burning and hydrometallurgical processing with ammonium acetate solution | |
| Yu et al. | A facile lead acetate conversion process for synthesis of high‐purity alpha‐lead oxide derived from spent lead‐acid batteries | |
| CN117383540A (en) | Preparation method of high-magnification modified biomass hard carbon material | |
| CN115418499A (en) | Method for enriching lithium from lithium-containing solution | |
| CN113666424B (en) | Precursor of sodium ion battery anode material and preparation method thereof | |
| CN118335927A (en) | A pre-lithiation silicon-oxygen composite material, preparation method, negative electrode sheet and lithium-ion battery | |
| WO2023116019A1 (en) | Lithium iron phosphate material and preparation method therefor | |
| CN1100153A (en) | Method for removal of copper from electrolytic nickel anodic liquid | |
| JP3590178B2 (en) | Electrolytic manganese dioxide, method for producing the same, and manganese dry battery | |
| CN113998686B (en) | Polyamide-amine dendritic polymer surface modified carbon material and preparation method and application thereof | |
| CN105226343A (en) | With the lead-containing compounds in waste lead accumulator for the method for positive plate of lead storage battery prepared by raw material | |
| CN108786713A (en) | A kind of nano hydroxyapatite adsorbent and its preparation method and application that parents' absorbent-type is sulfhydryl modified | |
| CN1234622A (en) | Process of surface cobalt-coating for high-density ball-shape nickel hydroxide | |
| CN1588676A (en) | Method for coating and mixing metal M alpha-Co(OH)2 on ball shape nickel hydroxide surface | |
| CN112864384A (en) | Preparation method and application of positive electrode material lithium iron phosphate | |
| CN109659535A (en) | A kind of molybdenum carbide/carbon composite and its preparation method and application | |
| CN1078185A (en) | Make the wet type amalgamation method of amalgam zinc powder | |
| CN106540649A (en) | Green synthesis and application of a manganese-calcium nanoadsorbent constructed from egg shells | |
| CN114759182A (en) | Graphene-coated tin oxalate negative electrode material, preparation method thereof and battery | |
| CN114927683A (en) | Prussian blue positive electrode material of sodium ion battery and preparation method of Prussian blue positive electrode material |
Legal Events
| Date | Code | Title | Description |
|---|---|---|---|
| C06 | Publication | ||
| PB01 | Publication | ||
| C10 | Entry into substantive examination | ||
| SE01 | Entry into force of request for substantive examination | ||
| C10 | Entry into substantive examination | ||
| SE01 | Entry into force of request for substantive examination | ||
| C14 | Grant of patent or utility model | ||
| GR01 | Patent grant | ||
| C15 | Extension of patent right duration from 15 to 20 years for appl. with date before 31.12.1992 and still valid on 11.12.2001 (patent law change 1993) | ||
| OR01 | Other related matters | ||
| C19 | Lapse of patent right due to non-payment of the annual fee | ||
| CF01 | Termination of patent right due to non-payment of annual fee |